THE IMPORTANCE OF EMPLOYEE MOTIVATION AND JOB SATISFACTION - Nurazlin Binti Sulaiman; Nurul Ain Jasmin Binti Mohd Jailani; Nurhidayatul Jannah Binti Saari; Nur Najiha Safia Binti Zanal Abdin; Siti Nur Hamizah Binti Zainal Abidin; Noorhafizzatul Ain Binti Mohd Norizan; Nurhafizah Binti Mohd Zolkapli (International Journal of Accounting, Finance and Business, 2022)
In today's business world, committed employees become a pillar of a successfulorganization, and this commitment usually comes from employee motivation and jobsatisfaction. It usually creates energy to drive employees towards organizational objectives andgoals. Without an employee’s commitment, it would be impossible to achieve an organization’sperformance. Thus, this paper has been written to purposely explore the link between twoimportant variables, which are employee motivation and job satisfaction. In accomplishing theobjective of this review paper, a comprehensive review has been carried out on the empiricalstudy papers or articles cited in online databases such as the UiTM database system,ResearchGate, and Google Scholar. The articles that have been chosen and reviewed rangedbetween 2016 and 2022. Although various studies have been conducted on the relationshipbetween employee motivation and job satisfaction, the extent to which the two are linked hascontinued to be a source of intense debate among scholars. Hence, this paper aims at presentingreviews of the existing and past literature on employee motivation and job satisfaction. Thereview will give a holistic understanding of the employee motivation and job satisfactionconcept for future researchers and aid them in recognizing the research gap.